PENGARUH BANGSA SAPI POTONG TERHADAP JENIS CACING YANG MENGINFEKSI TERNAK YANG DISEMBELIH DI RUMAH POTONG HEWAN GIWANGAN YOGYAKARTA - , ARIKUNTO PADMADEWA; , Prof. Dr. Ir. Endang Baliarti, SU. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Worm disease is a major problem for beef cattle farms in Indonesia. Cases of worm infection that attack the beef cattle on the ranch people could lead to decline in the cattle quality and mortality when the worm quantity is over. This research was carried out to know the influence of beef cattle strain about worm type infected cattle were slaughtered in Giwangan Animals Slaughtering House Of Yogyakarta. The materials used 60 feses cattles consist of Peranakan Ongole (PO), Simmental Peranakan Ongole (SimPO) and Limousin Peranakan Ongole (LimPO), 20 each. Feses examination method used the Sentrifuse test, Parfitt and Banks as well as McMaster test, in the laboratory section of Parasitology, Faculty of veterinary, University of Gadjah Mada, Yogyakarta. The results showed by the worm infection of 58%. Cattle sample were worm and parasite is strain PO 30.8%, SimPO and LimPO 34.6% infection of Strongyle worm 34%, Fasciola sp. 29%, parasite Coccidia protozoa 23% Trichuris sp. 6%, Moniezia sp. and Paramphistomum sp. 4%. Concluded of this study there was distinction the beef cattle influencing worm type that infects.